2021
DOI: 10.3389/fcell.2021.630361
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Kcnj16 in Mice Does Not Alter Auditory Function

Abstract: Endolymphatic potential (EP) is the main driving force behind the sensory transduction of hearing, and K+ is the main charge carrier. Kir5.1 is a K+ transporter that plays a significant role in maintaining EP homeostasis, but the expression pattern and role of Kir5.1 (which is encoded by the Kcnj16 gene) in the mouse auditory system has remained unclear. In this study, we found that Kir5.1 was expressed in the mouse cochlea. We checked the inner ear morphology and measured auditory function in Kcnj16–/– mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Sensorineural hearing loss is caused by many factors that impair hair cell and spiral ganglion neuron function [23][24][25][26][27][28], including ototoxic drugs, genetic factors, aging, noise exposure, and chronic cochlear infections [29][30][31][32][33]. A growing amount of evidence has demonstrated that PIN1 plays critical roles in aging-associated diseases [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Sensorineural hearing loss is caused by many factors that impair hair cell and spiral ganglion neuron function [23][24][25][26][27][28], including ototoxic drugs, genetic factors, aging, noise exposure, and chronic cochlear infections [29][30][31][32][33]. A growing amount of evidence has demonstrated that PIN1 plays critical roles in aging-associated diseases [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…HCs in the inner ear cochlea function in transducing sound waves into electric signals [17][18][19][20][21], while supporting cells function in supporting the HCs and providing the potential pool for HC regeneration [22][23][24][25][26]. Damages from a variety of sources can impair HC function, including genetic factors, aging, ototoxic drugs, chronic cochlear infections, and noise exposure [19,[27][28][29][30][31]. In this study, we reported the protective effect of Clusterin deficiency against age-related hearing loss and drug-induced ototoxicity, which are both due to irreversible loss of sensory HCs [32][33][34][35][36] and degeneration of the spiral ganglion neurons (SGNs) [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…HC transduces the sound waves into electric signals (Qi et al, 2019), while SGNs transfer these signals into the auditory cortex to have the hearing ability (Guo et al, 2016, 2019, 2020). WHO reported that 466 million people are suffering with hearing loss worldwide, caused by genetic factors, infectious diseases, chronic cochlear infections, aging, exposure to noise, and ototoxic drugs (He et al, 2017(He et al, , 2020Tan et al, 2019;Zhang et al, 2020;Zhou et al, 2020;Lv et al, 2021); for children from 6 to 19 years old, the estimated CSSD incidence was 0.7-0.8%. In this study, we reported a Bama miniature pedigree with high and stable incidence of CSSD, which reached 46.67% under the mating mode of paternal CSSD with maternal CSSD pigs.…”
Section: Discussionmentioning
confidence: 99%